Flood Hazard Mapping and Flood Vulnerability Analysis of Building Structures at Settlement-scale - Lamichhane, Suraj; Devkota, Nirajan; Poudel, Hari Prasad; Luitel, Somnath (Journal of Science and Engineering, 2024)
This research investigates flood hazards and vulnerabilities in Sauraha region of Nepal, employing a multidisciplinary methodology. Hydrological studies, field surveys, and hydraulic modeling were conducted to assess historical floods, estimate flood discharges, and analyze building vulnerabilities. Findings indicate that major tributaries substantially contribute to flood flow, with the East Rapti River posing a significant risk. Gumbel's distribution and Log Pearson's III distribution provided anticipated flood discharges for various return periods, illuminating the severity of potential inundation. Hydraulic simulations forecasted extensive inundation during a 100-year return flood, especially along the riverbanks, impacting commercial structures and tourist attractions. Vulnerability assessments revealed that 75% of riverside buildings face extreme vulnerability during such events. Urgent flood protection initiatives, including mandating flood-resilient building designs and preserving natural drainage systems, are imperative. The study identifies limitations, suggesting detailed assessments and sophisticated modeling for comprehensive flood mitigation strategies. Overall, this study underscores the immediate need for targeted interventions to address the persistent and complex flood dynamics in Sauraha.